PENGEMBANGAN MODEL PEMBELAJARAN GETARAN BERBASIS VIDEO YOUTUBE UNTUK MENINGKATKAN PEMAHAMAN KONSEP MAHASISWA POLITEKNIK - I Gede Rasagama (Pendidikan Kimia Unimus, 2020)
This study aims to find out: (i) video-based vibration learning model from http://youtube.com to improve concept understanding; (ii) the feasibility of the learning model; and (iii) strengths and weaknesses of the learning model. Research using the R&D approach includes 4 phases. The results showed: (i) the learning model was divided into: preliminary phases, core activities, and closing phases, containing objectives, sequence of material, and discussion based on student questions; (ii) an expert assesses the model is correct in the category: